PROMOTION OF PEOPLE’S POLITICAL PARTICIPATION AT TA KHAN SUBDISTRICT, BAN KHAI DISTRICT, RAYONG PROVINCE - Arunrat, Prueksasee; Chansilp, Vacharin; Chatchorfa, Apinyar (Journal of MCU Nakhondhat, 2024)
This research article aims to: 1) Examine the level of political participation promotion among citizens, 2) Compare the promotion of political participation among citizens, classified by personal factors, and 3) Explore the application of Buddhist principles to enhance political participation. The research employs a mixed-method approach, incorporating both quantitative and qualitative methods. The population consists of 7,663 citizens in Takhun Subdistrict, Ban Khai District, Rayong Province. A sample size of 381 individuals was selected using Taro Yamane’s formula. Questionnaires were used to collect data, and the analysis was performed using frequency, percentage, mean, standard deviation, and t-test and F-test. For the qualitative part, data were gathered from 9 key informants through in-depth interviews and analyzed descriptively. The study results showed that: 1) The overall level of promoting political participation among citizens was high. 2) Citizens of different ages, educational backgrounds, and occupations exhibited significantly different levels of political participation at the 0.05 level of statistical significance, while there were no significant differences in political participation based on gender and income. 3) The application of the "Aparihaniya Dhamma" (principles of non-decline) to promote political participation can be achieved by fostering community unity, regularly conducting meetings and discussions, respecting the opinions of elders and leaders, promoting unified decision-making, and encouraging open participation by all citizens. These principles help build trust and cooperation in society, resulting in increased citizen enthusiasm for political participation.